"Living in the Moment": The 'Bushman' Presence, Past and Future. Issue 1 (2nd January 2018) - Voss, Tony
Abstract : State and society's perhaps guilty recognition of the San in the coat of arms of post-apartheid South Africa was accompanied by a scholarly and creative revival of interest in the San's poetic and material legacy. Two recent books explore that legacy. Helize van Vuuren's A Necklace of Springbok Ears, which argues for the parity of Von Wielligh's Boesmanstories with the work of Bleek and Lloyd, shows that writers, drawing inspiration from !Xam orality, have enriched our literature and reached towards its integrity and continuity with its historic (and perhaps pre-historic) past. In a global perspective, James Suzman's Affluence without Abundance, an anthropologist's account of his life with the Ju/'hoansi of Namibia, revives and revitalises the argument that twenty-first-century humanity can learn and benefit from the morality and the ecology of hunter-gatherers, suggesting that in some survivors, their critical and creative imagination continues to sustain their cultural heritage.